Preparation method of self-forming 3D curved glass based on single-sided film plating ion barrier
Patent Information
- Application Number
- CN202611294125.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-25
- Publication Date
- 2026-10-16
AI Technical Summary
因机械冷弯工艺依靠外力强制弯折成型,玻璃内部会留存大量不可逆的残余拉应力,应力分布不均,长期使用易导致曲面玻璃出现应力松弛、曲面回弹或翘曲变形,尺寸稳定性较差;并且曲面玻璃的弯折区域易产生局部应力集中,抗冲击能力弱、易开裂破碎;受弹性回弹特性影响,产品的短边拱度、平面度精度较差,无法满足高精度装配要求;残余应力还会加速玻璃基材老化,缩短产品使用寿命
[0008]This invention differs from traditional high-temperature hot bending and high-temperature softening molding. It eliminates the need for high-temperature molding deformation at the glass's softening point, employing only conventional chemical strengthening temperatures. This preserves the original surface structure of the glass, resulting in superior optical quality with no optical ripples, distortion, or surface pitting. It also eliminates the risk of nickel sulfide-induced spontaneous breakage caused by high temperatures. Furthermore, it eliminates the need for customized curved surface forming molds of various curvatures, saving on mold opening, maintenance, and replacement costs, reducing dimensional deviations caused by molds, and significantly improving mass production yield. This invention also differs from traditional mechanical cold bending, which uses external force to force bending. It relies on the intrinsic stress difference created by the difference in ion exchange on both sides to drive the glass's spontaneous bending. After forming, there is no irreversible residual tensile stress caused by mechanical forced bending, preventing stress relaxation, surface springback, warping deformation, and localized stress concentration cracking. The finished product's dimensional stability, crack resistance, and long-term weather fatigue life are significantly improved. Finally, this invention has a simple process path, requiring only one tempering treatment, simplifying the production steps of curved glass, shortening the production cycle, and improving production efficiency.
Smart Images

Figure CN122916451A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of curved glass processing and production technology, and in particular to a method for preparing self-forming 3D curved glass based on single-sided ion-barrier coating. Background Technology
[0002] Curved glass is widely used in the mobile phone, automotive, and construction industries, especially in the automotive industry, where the touch display cover glass requires high surface quality from curved glass. Currently, the mass production molding processes for 3D curved glass are mainly divided into two categories: high-temperature hot bending and mechanical cold bending. Both of these processing techniques have shortcomings that restrict the improvement of high-end curved glass quality and cost control.
[0003] Traditional high-temperature hot bending processes achieve curved glass surfaces by heating 2D glass to its softening point, pressing it with a mold, and then cooling it. However, high-temperature forming is susceptible to the effects of temperature field and mold errors, which can lead to optical ripples, distortions, or pitting, resulting in poor optical consistency. Furthermore, temperature differences can easily cause internal stress disturbances in the glass, and combined with nickel sulfide impurities, this can easily trigger spontaneous glass breakage, leading to a decrease in mass production yield. In addition, glass products with different curvatures require customized molds, which have long development cycles, high costs, and poor versatility. At the same time, high temperatures can damage the original dense surface layer of the strengthened glass, resulting in a significant reduction in the glass's hardness, wear resistance, impact resistance, and weather resistance.
[0004] Traditional mechanical cold bending, also known as the Kanglin cold bending process, is a room-temperature forced bending forming process. While it avoids high-temperature damage, it suffers from serious mechanical stress defects. Because mechanical cold bending relies on external force to force bending, a large amount of irreversible residual tensile stress remains inside the glass. This uneven stress distribution can easily lead to stress relaxation, springback, or warping deformation in curved glass over long-term use, resulting in poor dimensional stability. Furthermore, the bending area of curved glass is prone to localized stress concentration, weakening its impact resistance and making it susceptible to cracking and breakage. Due to the elastic rebound characteristics, the short-side camber and flatness accuracy of the product are poor, failing to meet high-precision assembly requirements. Residual stress also accelerates the aging of the glass substrate, shortening the product's lifespan.
[0005] Chinese invention patent application CN110818281A discloses a 3D glass and its manufacturing method. The manufacturing method includes the following steps: subjecting a flat glass to a first chemical tempering treatment; forming a dense film layer on one side of the flat glass after the first chemical tempering treatment; subjecting the flat glass with the dense film layer to a second chemical tempering treatment; and cooling the glass after the second chemical tempering treatment to obtain 3D glass. This invention's manufacturing method involves first subjecting the flat glass to a first chemical tempering treatment, then forming a dense film layer on the flat glass, and then performing a second chemical tempering treatment. During the second tempering, the different states on the two sides lead to different ion exchange rates, causing the glass to bend into a certain arc, achieving the effect of producing 3D glass. Although this invention's technical solution differs from traditional high-temperature hot bending and mechanical cold bending processes by changing the ion exchange rates on both sides of the glass to form curved glass, its technical solution requires two chemical tempering treatments on the flat glass, which is not conducive to improving processing efficiency and saving processing costs. Summary of the Invention
[0006] The technical problem to be solved by the present invention is to provide a method for preparing self-forming 3D curved glass based on single-sided coating ion barrier, which can simplify the processing steps of curved glass.
[0007] To solve the above-mentioned technical problems, the technical solution adopted by the present invention is: a method for preparing self-forming 3D curved glass based on single-sided ion-barrier coating, comprising the following steps: S1. Select glass sheets and perform pretreatment to obtain glass substrates; S2. A single or multiple composite inorganic barrier film is deposited on one side of a glass substrate using a vacuum magnetron sputtering process, while the other side of the glass substrate is not coated. S3. Place the glass workpiece obtained after single-sided coating into a strengthening fixture and send it into a potassium nitrate molten salt furnace for constant temperature ion exchange strengthening. S4. After strengthening, allow the glass workpiece to cool naturally to room temperature, then clean and dry it.
[0008] This invention differs from traditional high-temperature hot bending and high-temperature softening molding. It eliminates the need for high-temperature molding deformation at the glass's softening point, employing only conventional chemical strengthening temperatures. This preserves the original surface structure of the glass, resulting in superior optical quality with no optical ripples, distortion, or surface pitting. It also eliminates the risk of nickel sulfide-induced spontaneous breakage caused by high temperatures. Furthermore, it eliminates the need for customized curved surface forming molds of various curvatures, saving on mold opening, maintenance, and replacement costs, reducing dimensional deviations caused by molds, and significantly improving mass production yield. This invention also differs from traditional mechanical cold bending, which uses external force to force bending. It relies on the intrinsic stress difference created by the difference in ion exchange on both sides to drive the glass's spontaneous bending. After forming, there is no irreversible residual tensile stress caused by mechanical forced bending, preventing stress relaxation, surface springback, warping deformation, and localized stress concentration cracking. The finished product's dimensional stability, crack resistance, and long-term weather fatigue life are significantly improved. Finally, this invention has a simple process path, requiring only one tempering treatment, simplifying the production steps of curved glass, shortening the production cycle, and improving production efficiency.
[0009] As an improvement to the above scheme: in step S1, the glass substrate is an aluminosilicate glass substrate or a lithium aluminosilicate glass substrate; the thickness of the glass substrate is 0.4–1.3 mm. This invention uses aluminosilicate glass or lithium aluminosilicate glass as raw material, ensuring that the glass matrix contains sufficient exchangeable alkali metal ions. This allows for the formation of a compressive stress layer of sufficient depth and size during molten salt ion exchange, ensuring that the bare surface can generate sufficient compressive stress and form a significant stress difference with the coated side, thus guaranteeing that the glass can be successfully and spontaneously bent into shape. Lithium aluminosilicate glass can also achieve deeper ion exchange, further widening the adjustable curvature range. Because if the thickness of the glass sheet is too small, the glass rigidity is insufficient, and deformation can easily become uncontrollable and the uniformity of the curved surface can deteriorate after molding. On the other hand, if the thickness of the glass sheet is too large, a large double-sided stress difference is required to drive bending, and the ion exchange conditions are difficult to achieve, making molding difficult. Therefore, this invention limits the thickness of the glass sheet to 0.4 to 1.3 mm. This thickness range takes into account the actual thickness requirements of mobile phone and terminal cover products, while also taking into account the feasibility of stress self-forming, ensuring uniform and controllable curved surface molding, and can be adapted to the mainstream product specifications of consumer electronics 3D glass cover.
[0010] As an improvement to the above solution: In step S1, the pretreatment process includes chamfering and trimming of the glass substrate using CNC precision carving, edge polishing, ultrasonic cleaning, and hot air drying. This invention, through CNC precision carving chamfering and trimming combined with edge polishing, can effectively eliminate edge chipping, burrs, and microcracks in the glass. Since microcracks at the glass edge are a significant source of stress-induced cracking, eliminating edge defects through pretreatment can improve the overall impact and crack resistance of the finished product, preventing damage from the edges during subsequent coating, strengthening, and self-forming stages, thus improving mass production yield. This invention thoroughly removes dust, oil, and particulate impurities from the glass surface through ultrasonic cleaning combined with hot air drying. If contaminants are present on the glass substrate surface, it can cause pinholes, film peeling, and localized barrier failure during subsequent magnetron sputtering coating, leading to localized ion exchange abnormalities, resulting in localized surface distortion and inconsistent forming. This invention ensures a clean glass substrate surface through pretreatment, guarantees a dense and complete inorganic barrier film layer, ensures stable single-sided ion barrier effect, and ultimately obtains a uniform and consistent curved surface shape throughout the entire surface area.
[0011] As an improvement to the above scheme: In step S2, the composite inorganic barrier film is made of at least one of silicon dioxide, titanium dioxide, and silicon nitride; the thickness of the inorganic barrier film is 10–300 nm. This invention limits the material of the inorganic barrier film to include silicon dioxide, titanium dioxide, and silicon nitride, all of which are dense inorganic materials with good chemical stability. They exhibit excellent high-temperature resistance and molten salt corrosion resistance under the potassium nitrate molten salt strengthening temperature environment of 400–420°C, and will not be damaged by molten salt erosion. Furthermore, they can effectively prevent potassium ions from penetrating and replacing into the glass interior, thus suppressing ion exchange on the coating side and reliably constructing differences in ion exchange depth and stress magnitude on both sides, providing a basis for the self-forming of curved glass. If the film thickness is less than 10 nm, pinhole defects are likely to occur, resulting in insufficient ion blocking ability. A large amount of ion exchange still occurs on the coated side, and the stress difference between the two sides is insufficient, making effective bending impossible. If the film thickness is greater than 300 nm, the internal stress of the film increases, and the film itself is prone to cracking and peeling, losing its blocking effect. At the same time, excessively thick film will affect the optical transmittance of glass. Therefore, this invention limits the film thickness to 10-300 nm. Within this thickness range, the reliability of ion blocking, the quality of film formation, and the optical transmittance of the product can be balanced. The ion blocking ability can be easily adjusted by adjusting the film thickness, thereby controlling the stress difference between the two sides and achieving controllable adjustment of the forming curvature.
[0012] As an improvement to the above scheme: In step S3, the strengthening temperature of isothermal ion exchange strengthening is 400-420℃, and the strengthening time is 3-5 hours. This invention limits the strengthening temperature of isothermal ion exchange strengthening because this temperature range falls within the conventional working temperature range for glass chemical strengthening, which is far below the glass softening temperature. This prevents high-temperature thermal deformation of the glass and effectively avoids optical defects and surface damage caused by traditional hot bending processes. If the temperature is too low, the potassium-sodium ion replacement reaction rate is slow, making it difficult to form a sufficiently deep compressive stress layer on the bare surface, resulting in insufficient stress difference between the two sides and inability to drive effective bending. If the temperature is too high, it will accelerate the relaxation of the glass matrix structure, causing compressive stress to easily relax and decay, leading to poor stress stability and exacerbating the risk of film thermal failure. Therefore, the temperature range limited by this invention can balance ion exchange reaction efficiency and stress stability.
[0013] As an improvement to the above solution: In step S4, pure water and a weakly alkaline cleaning agent are used to clean the glass workpiece. Since potassium nitrate molten salt residue easily adheres to the glass surface after strengthening, if this residue remains on the glass surface, it will corrode the inorganic barrier film, causing localized damage and disrupting the stress system formed by the single-sided ion barrier. Furthermore, residual salt impurities will cause dirt and white spots on the glass surface, affecting its appearance and optical performance. This invention uses a weakly alkaline cleaning agent combined with pure water to clean the glass workpiece, which can efficiently dissolve and remove molten salt residue without corroding the silica, titanium dioxide, or silicon nitride inorganic barrier films, and without damaging the glass substrate. It not only thoroughly removes molten salt impurities but also protects the integrity of the film, ensuring that the internal stress of the glass can smoothly achieve stress self-balancing without external interference. This ensures that the glass spontaneously bends and shapes to obtain 3D curved glass products with uniform dimensions and curvature, improving the finished product's appearance yield and reliability.
[0014] The beneficial effects of this invention are as follows: By improving the forming process of 3D curved glass, a dense inorganic barrier coating layer is prepared on one side of the glass substrate. This coating layer effectively blocks the penetration and replacement of potassium ions under high temperature conditions, significantly reducing the ion exchange rate and penetration depth on the coated side. Meanwhile, the uncoated exposed side of the glass substrate has no barrier and can normally complete potassium and sodium ion replacement, forming a high-stress, deep compressive stress layer. This results in a stable and controllable compressive stress difference between the two sides of the glass substrate, causing an imbalance in the internal stress distribution of the glass. To achieve stress self-balancing, the glass will continuously and slowly bend towards the coated side with lower compressive stress and a shallower stress layer, ultimately forming a uniformly shaped 3D curved glass. The process path of this invention is simple, requiring only one tempering treatment, which simplifies the production steps of curved glass, shortens the production cycle, and improves production efficiency. Attached Figure Description
[0015] Figure 1This is a schematic diagram of the pretreated glass substrate in this invention; Figure 2 This is a schematic diagram showing the difference in ion exchange between the two sides of the glass workpiece during the strengthening stage in this invention. Figure 3 This is a schematic diagram of a glass workpiece after being bent and shaped under stress self-balancing in this invention.
[0016] The markings in the diagram are: 100 - glass substrate, 200 - inorganic barrier film layer, 310 - coated surface, 320 - uncoated surface. Detailed Implementation
[0017] To facilitate understanding of the present invention, the present invention will be further described below in conjunction with the accompanying drawings and embodiments.
[0018] In the description of this invention, it should be noted that the terms "front", "rear", "left", "right", "up", "down", "inner", etc., indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings, and are only for the convenience of description, and do not indicate or imply that the device or component referred to must have a specific orientation, or be constructed and operated in a specific orientation, and therefore should not be construed as a limitation of this invention.
[0019] The method for preparing self-forming 3D curved glass based on single-sided ion-barrier coating disclosed in this invention is carried out in the following steps: S1. Select glass sheets and pre-process them according to the product size to obtain glass substrate 100. The glass sheets are selected as aluminosilicate glass sheets or lithium aluminosilicate glass sheets with a thickness of 0.4-1.3mm. During the pre-processing, the chamfering and edge trimming are completed by CNC precision carving, and then the burrs are removed by edge polishing. Finally, after ultrasonic multi-segment cleaning, hot air drying is performed to thoroughly remove dust, oil, and impurities from the glass surface, ensuring that the glass substrate surface is clean and flat, without any contaminants affecting the subsequent coating and strengthening effects.
[0020] S2, such as Figure 1 As shown, a single or multiple composite inorganic barrier film 200 is deposited on one side of a glass substrate 100 using a vacuum magnetron sputtering process. The inorganic barrier film 200 is made of one or more of silicon dioxide, titanium dioxide, and silicon nitride. The thickness of the inorganic barrier film 200 is controlled to be 10–300 nm. The entire coating process is carried out in a high-vacuum, dust-free environment to ensure that the film is dense, uniform, free of pinholes, cracks, and peeling, and to stably achieve the alkali metal ion blocking effect. The other side of the glass substrate 100 is completely exposed and is not coated.
[0021] S3. Place the glass workpiece obtained after single-sided coating into a strengthening fixture and send it into a potassium nitrate molten salt furnace for isothermal ion exchange strengthening; the strengthening temperature of isothermal ion exchange strengthening is controlled at 400-420℃, and the strengthening time is 3-5 hours. Figure 2 As shown, the uncoated surface 320 of the glass workpiece undergoes full potassium and sodium ion exchange under high temperature conditions, forming a high-pressure stress and a deep stress layer; while the coated surface 310 of the glass workpiece is blocked by the inorganic barrier film layer 200, resulting in a significant reduction in ion exchange efficiency, and can only form a low-pressure stress and a shallow stress layer; ultimately, a stable stress difference is formed on both sides of the glass workpiece.
[0022] S4. After strengthening, remove the glass workpiece from the potassium nitrate molten salt furnace and allow it to cool naturally to room temperature. Then, clean the surface of the glass workpiece with pure water and a weak alkaline cleaning agent to remove any remaining molten salt impurities. After cleaning, dry it with hot air. In this step, under normal temperature conditions, such as... Figure 3 As shown, the glass workpiece gradually completes the internal stress balance, spontaneously bends uniformly towards the coating side, and the stress is completely stable within 24 hours, forming a 3D curved glass product with uniform curvature and no distortion.
[0023] Example
[0024] Taking the molding process of the 3D cover glass for the vehicle's central control as an example, aluminosilicate 2D glass with a thickness of 0.7mm and a product size of 777mm×165mm is selected. The process involves cutting, CNC chamfering, edge polishing, and ultrasonic cleaning and drying. Then, a single layer of silica film with a thickness of 20nm is deposited on one side of the glass using magnetron sputtering. The film layer is dense and defect-free. Next, the glass is sent to a potassium nitrate molten salt furnace for isothermal ion exchange strengthening. The molten salt temperature is 415℃, and the strengthening is carried out at the same temperature for 4 hours to complete the ion exchange. After strengthening, the glass is cooled to room temperature, the glass surface is cleaned, and then dried.
[0025] The stress test was performed on the 3D curved glass product obtained in this embodiment. The surface compressive stress CS on the exposed side of the glass was 920MPa, and the stress layer depth DOL was 42μm. The surface compressive stress CS on the coated side of the glass was 820MPa, and the stress layer depth DOL was 38μm. The stress difference between the two sides of the glass was 100MPa. The glass spontaneously and uniformly bent towards the coated side, with a forming curvature radius R of 3000mm, a short side flatness of 0.3mm, a smooth curved surface without distortion or warping, a light transmittance of 91.2%, no mechanical processing marks on the appearance, and excellent structural strength.
[0026] Obviously, the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.
Claims
1. A method for preparing self-forming 3D curved glass based on single-sided ion-barrier coating, characterized in that: Includes the following steps: S1. Select glass sheets and perform pretreatment to obtain glass substrates; S2. A single or multiple composite inorganic barrier film is deposited on one side of a glass substrate using a vacuum magnetron sputtering process, while the other side of the glass substrate is not coated. S3. Place the glass workpiece obtained after single-sided coating into a strengthening fixture and send it into a potassium nitrate molten salt furnace for constant temperature ion exchange strengthening. S4. After strengthening, allow the glass workpiece to cool naturally to room temperature, then clean and dry it.
2. The method for preparing self-forming 3D curved glass based on single-sided ion-barrier coating as described in claim 1, characterized in that: In step S1, the glass substrate is an aluminosilicate glass substrate or a lithium aluminosilicate glass substrate; the thickness of the glass substrate is 0.4 to 1.3 mm.
3. The method for preparing self-forming 3D curved glass based on single-sided ion-barrier coating as described in claim 1, characterized in that: In step S1, the pretreatment process includes chamfering and trimming of the glass sheet by CNC precision carving, edge polishing, ultrasonic cleaning, and hot air drying.
4. The method for preparing self-forming 3D curved glass based on single-sided ion-barrier coating as described in claim 1, characterized in that: In step S2, the inorganic barrier film is made of at least one of silicon dioxide, titanium dioxide, and silicon nitride; the thickness of the inorganic barrier film is 10–300 nm.
5. The method for preparing self-forming 3D curved glass based on single-sided ion-barrier coating as described in claim 1, characterized in that: In step S3, the strengthening temperature of isothermal ion exchange enhancement is 400-420℃, and the strengthening time is 3-5h.
6. The method for preparing self-forming 3D curved glass based on single-sided ion-barrier coating as described in claim 1, characterized in that: In step S4, pure water and a weak alkaline cleaning agent are used to clean the glass workpiece.
Citation Information
Patent Citations
3D glass and manufacturing method thereof
CN110818281A